Genome wide association study of shell growth, condition index, shell and mantle colour in the Portuguese oyster, Crassostrea angulata - Sang Van Vu; Wayne O’Connor; In Van Vu; Cedric Gondro; Thu Thi Anh Nguyen; Shantanu Kundu; Kim Hyun Woo; Soo Rin Lee; Tran Dang Khanh; Tiep Khac Nguyen; Hien Van Doan; Hsu Htoo; et al. (Aquaculture International, 2025)
The Portuguese oyster ( Crassostrea angulata ) is a commercially significant aquaculture species, gaining rapid popularity, particularly in Asia. Growth-related traits, along with shell and mantle colouration, are key determinants of market value in farmed oysters. To support trait improvement in breeding programs, this study investigates the genetic architecture of economically important traits, including shell length, shell height, shell width, condition index, and shell and mantle colour using genome-wide association study (GWAS). Using DArTseq technology, 647 oyster samples from two generations of a breeding program in Vietnam were genotyped: 188 samples from 57 full-sib families in the first generation and 459 samples from 33 full-sib families in the second. GWAS identified 31 significant SNPs associated with various traits, 24 of which mapped to protein-coding genes. Notable candidate genes associated with growth traits included CE128-like ( LOC128177318 ) and WIPI3-like ( LOC128167327 ), implicated in protein localization and autophagy, respectively. For colour-related traits, key candidate genes included glucose dehydrogenase ( LOC128184820 ), Neurobeachin-like ( LOC128156661 ), and POP1-like ( LOC128164428 ), which are linked to catalytic activities, membrane trafficking, and RNA processing, suggesting roles in pigmentation and biomineralization. Additionally, Neo-calmodulin-like ( LOC128183296 ), a gene involved in calcium binding, was identified as a candidate for shell colour, consistent with findings in other oyster species. The small effect sizes of the significant SNPs across all traits suggest polygenic control, underscoring the potential of genomic selection for trait improvement. This study provides foundational insights to inform selective breeding programs aimed at enhancing growth and aesthetic traits in C. angulata , contributing to the sustainability and profitability of oyster aquaculture.